Dietary rumen-protected L-arginine or N-carbamylglutamate enhances placental amino acid transport and suppresses angiogenesis and steroid anabolism in underfed pregnant ewes - Hao Zhang; Xia Zha; Bei Zhang; Yi Zheng; Xiaoyun Liu; Mabrouk Elsabagh; Yi Ma; Hongrong Wang; Guihua Shu; Mengzhi Wang (Animal Nutrition, 2023)
This study aimed to investigate the effects of dietary supplementation of underfed Hu ewes from d 35 to 110 of gestation with either rumen-protected L-arginine (RP-Arg) or N-carbamylglutamate (NCG) on placental amino acid (AA) transport, angiogenic gene expression, and steroid anabolism. On d 35 of gestation, 32 Hu ewes carrying twin fetuses were randomly divided into four treatment groups, each consisting of eight ewes, and were fed the following diets: A diet providing 100% of NRC's nutrient requirements for pregnant ewes (CON); A diet providing 50% of NRC's nutrient requirements for pregnant ewes (RES); RES diet plus 5 g/d NCG (RES + NCG); or RES diet plus 20 g/d RP-Arg (RES + ARG). On the d 110 of pregnancy, blood samples were taken from the mother, and samples were collected from type A cotyledons (COT; the fetal portions of the placenta). The levels of 17β-estradiol and progesterone in the maternal serum and both the capillary area density (CAD) and capillary surface density (CSD) in type A COT were decreased in response to Arg or NCG supplementation when compared to the RES group. The concentrations of arginine, leucine, putrescine and spermidine in type A COT were higher (P < 0.05) in the RES + ARG or RES + NCG group than in the RES group. The mRNA expression levels of inducible nitric oxide synthase (iNOS) and solute carrier family 15, member 1 (SLC15A1) were increased (P < 0.05) while those of progesterone receptor (PGR) and fibroblast growth factor 2 (FGF2) were decreased in type A COT by supplementation with either NCG or RP-Arg compared to the RES group. The results suggest that providing underfed pregnant ewes from d 35 to 110 of gestation with a diet supplemented with NCG or RP-Arg improves placental AA transport, and reduces the expression of angiogenic growth factor genes and steroid anabolism, leading to better fetal development.